Allelopathic effects of Androstachys johnsonii Prain on germination and growth of Zea mays L. and Vigna subterranea (L.) Verdc. - Mokganya, Mokgaetji Georginah; Ligavha-Mbelengwa , Hadzhi Maanda (Technium Social Sciences Journal, 2022)
Allelopathic effects of the donor plants are mostly regarded as harmful to target plants such as traditional crops. Traditional crops play pivotal role as staple food for rural communities and hence ensuring food security. Study of the allelopathic effects of Androstachys johnsonii Prain on the germination and growth of Zea mays L. and Vigna subterranea (L.) Verdc was conducted. Different plant leachates concentrations of 0.675%, 1.25%, 2.5% and 5% were prepared through serial dilutions. Germination bioassays were arranged in a complete randomized setup of three replicates for each treatment for seven days. Germination rates were calculated, radicle and hypocotyl lengths were also measured. Germination rates of Z. mays L. and V. subterranea (L.) Verdc. ranged from 50 - 100% and 18 - 76%, respectively. Significant differences of P< 0.005 were noticed from the germination rates of V. subterranea (L.) Verdc subjected to high concentrations of different extracts used. Statistically there was no significant differences between germination rates of Z. mays L. treated with all concentrations of leaf leachates against germination rates of the seeds treated with distilled water. Outstandingly, the germination rate and early growth of Z. mays L. were promoted by less concentrated extracts of leaf, root, stem bark and soil which then suggest future use of allelochemicals from Androstachys johnsonii Prain for promotion of maize plant productions. Based on the beneficial attributes of allelochemicals from Androstachys johnsonii on the germination and growth of Z. mays L., planting of Androstachys johnsonii Prain in maize fields is highly recommended.